Zambezi River System, from source to sink: a record of plateau and dome uplifts related to mantle dynamic and climate changes - (:unkn) unknown (My University, 2019)
The Zambezi System has been studied from its upstream catchment to the distal part of its deep-sea fan from 145Ma (Cretaceous to today), in the frame of the PAMELA project (Passive Margin Experiment Laboratory) fundedby TOTAL and IFREMER. This study was based offshore for the sink, on the sequence stratigraphic analysis of anextensive dataset of seismic lines calibrated on re-dated wells and onshore for the source, on a geomorphologicalanalysis of the stepped planation surfaces.The geological history can be summarized as follows. (1) The Lower Cretaceous is characterized by a decreaseof the sediment supply from 46 000 to 16 000 km3/Ma, at time of the margin topographic differentiation. (2) TheLate Cretaceous-Paleocene is characterized by three major uniformities intra-Cenomanian, uppermost Santonianand around the K-T boundary and is coeval with an increase of the sedimentary flux (21 000 km3/Ma) located intwo depocenters, north of the Limpopo Plain and below the modern Zambezi Delta. (3) The Eocene period is aperiod of carbonate production and of sharp decrease of the siliciclastic flux (3 000 km3/Ma). (4) The Late Eocene(up to today) is the birth of the modern Zambezi Delta characterized by a dramatic increase of the sedimentaryflux, from 13 000 km3/Ma (Oligocene) to 78 000 km3/Ma (Plio-Pleistocene) with three major unconformities atbase Early Miocene, base Late Miocene and base Pliocene.The efficiency of the sediment transport toward the deepest part of the sedimentary system - i.e. the ratio betweenthe volume of sediment in the delta and the one in the deep-sea-fan - changed trough time with three periods ofefficient transport during the Late Cretaceous, the Late Miocene and the Early Pliocene.These changes of sedimentary systems reflect the deformation of the African Plate, with (1) a major uplift of theSouth African Plateau from Late Cenomanian to Campanian times due to the migration of Africa over the SouthAfrican superplume, (2) a period with no
Keywords: African Research